New synonyms, combinations and faunistic records in the genus Denierella Kaszab (Coleoptera: Meloidae) - Batelka, Jan; Hájek, Jiří (Zootaxa, 2015)
Taxonomy of the genus Denierella Kaszab, 1952 (Coleoptera: Meloidae: Epicautini) is evaluated. The following new synonyms and combinations (all from the genus Epicauta Dejean, 1834) are established: Denierella thailandica (Dvořák, 1996) comb. nov. = D. striolata Yang & Ren, 2007 syn. nov.; Denierella emmerichi (Pic, 1934) comb. nov. = D. serrata Kaszab, 1952 syn. nov.; Denierella promerotricha (Dvořák, 1996) comb. nov. A lectotype is designated for Epicauta emmerichi. Epicauta emmerichi yunnanensis Kaszab, 1960 is provisionally raised to E. yunnanensis stat. nov., until its status can be confirmed by the study of the holotype specimen. Five new country records, one new Chinese province record and two new Indian state records of six Denierella species are provided, and the distribution of all species included in this study is outlined. A checklist of the genus Denierella is provided and general problems in the taxonomy of Asiatic Epicautini are discussed.